O uso da fotografia no processo de ensino-aprendizagem na Educação Infantil: análise do livro “Enquanto o almoço não fica pronto...”, de Sonia Rosa - Oliveira, Lourismar Gonçalves de (Universidade Federal do Tocantins, 2024)
This research addresses the use of photography in the book “While lunch is not ready...”, by Sonia Rosa, intended for Early Childhood Education, with the general objective of reflecting on how children obtain knowledge through photos, in the sense of favoring the teaching and learning process. As specific objectives, we present a brief history of photography; we recognize it as a resource that collaborates in the referred process of young children (four and five years old); and we reflect on the challenges that can arise in the use of photography in the classroom. Therefore, this study is justified by the need to stimulate the teaching and learning process of children in Early Childhood Education, in accordance with National Common Curricular Basis (BNCC, in Portuguese abbreviation) (BRASIL, 2017) and the works of authors such as Gil (2002), Minayo (2009) and Jobim and Souza and Lopes (2002), under the bias of a bibliographical research and with a qualitative approach. It should be noted that the analyzed book is part of Itaú Social Project “Read for a Child” and is recommended for the aforementioned age group. In this way, we encourage (and reflect on) the use of photography in the educational work of Early Childhood Education.